NATURAL INCIDENCE OF ENTOMOPATHOGENIC FUNGUS Nomuraea rileyi ON Spodoptera frugiperda INFESTING CORN IN BENGKULU - Ginting, Sempurna; Zarkani, Agustin; Sumarni, Teten; Nadrawati, Nadrawati (Universitas Lampung, 2020)
Natural incidence of entomopathogenic fungus Nomuraea rileyi on Spodoptera frugiperda infesting corn in Bengkulu. Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) is a new invasive pest in corn. The intensive use of synthetic insecticides for pest control causing various problems such as resistance, pest resurgence, and environmental damage. To solve these problems, entomopathogenic fungi could be used as an alternative in pest management. Therefore, this study was aimed to determine the natural incidence of Nomuraea rileyi (Farlow) Samson (Hypocreales: Clavicipitaceae) entomopathogenic fungus on S. frugiperda in Bengkulu. The research was carried out by exploring the corn producing areas in Bengkulu for N. rileyi incidence. The results showed that the N. rileyi was occurred naturally infected S. frugiperda larvae reached 79.0%. Meanwhile, the percentage of crops damage due to S. frugiperda was ranged from 40.0 to 96.0%. The highest natural incidence of N. rileyi were found in the Village of Bukit Barisan and Tugu Rejo (79.0%), followed by Pulo Geto Baru (25.0%), and Taba Mulan (5.3%) while the lowest incidence was in Sidomulyo (1.0%). The infected larvae were not found in the Napal, Beringin Raya 1, and Beringin Raya 2, despite the percentage of S. frugiperda attacks was reached 50.0; 50.0 and 74.0%, respectively.